Pembuatan dan Pemasangan Plang Arah sebagai Upaya Peningkatan Identitas dan Sistem Navigasi di Desa Cempaka Mulia Timur - Wina Aisyawary; Novinda Al Islami; Moch. Catur Tri Kurniawan S; Hadma Yuliani (Indonesia Bergerak : Jurnal Hasil Kegiatan Pengabdian Masyarakat, 2024)
Real Work Lecture (KKN) is a form of education by providing learning experiences for students to live in the community, directly identifying and handling community problems in the village. One of the problems that occurred in Cempaka Mulia Timur Village was the need for a signpost to the village, this was needed because many people who wanted to visit the village did not know where it was, making it difficult for them to find the address they wanted to visit. The existence of a signpost can make it easier for people when visiting the Cempaka Mulia Timur Village area. A signpost is a name sign that aims to identify the location to be visited so that people who see the signpost can know exactly the direction to the hamlet location, be it villagers or other people visiting the village.